Navigating Obstacles in Dairy Production: A Comprehensive Analysis - Solomon Jebaraj, Trapty Agarwal, Apoorva Joshi (Revista Electronica de Veterinaria, 2024)
The production of dairy products is crucial in satisfying the worldwide demand for milk and its derivatives. Optimal dairy production requires the integration of breeding, nutrition, and technology improvements. There are constant obstacles that exist, including natural difficulties such as the influence of climate change on the quality of animal feed, as well as economic problems that affect the lives of farmers. To overcome these barriers, it is important to implement innovative strategies, adopt sustainable practices, and encourage collaboration within the dairy business. Embracing change, adopting technology, and emphasizing animal care are essential measures for ensuring a resilient and profitable future in the dairy industry. In this research, we gathered primary data from the Bhavnagar district, Gujarat. Ten villages, including Bhandariya, Nagdhaniba, and Sodvadra, were randomly selected from each area. A total of 200 dairy producers, each holding a minimum of two dairy animals, were surveyed on obstacles in animal farming procedures. The research highlighted a number of obstacles for dairy farmers in the Nagdhaniba region. Economic obstacles included payment issues (76.12%), insufficient finances (61.22%), and unaffordable animal feed (54.33%). Insufficient illness understanding (66%), limited availability to reproductive technologies (59.87%), and inadequate a veterinarian treatment (55.81%) were among the technical obstacles. Other constraints included the high cost of green animal feed (43.11%), a lack of drinking water (39.11%), and a shortage of milk storage facilities (23.15%). These findings highlight the varied characteristics of the obstacles restricting dairy production in the region.